Analysis of perspective for using chickpea seeds to produce functional food ingredients - Hevryk, Vladyslav; Kaprelyants, Leonid; Trufkati, Liudmyla; Pozhitkova, Liliia (Technology audit and production reserves, 2020)
The food industry is now increasingly focusing on changing existing technologies in order to improve the efficiency of raw materials processing and increase the production of high quality food products and functional ingredients with a minimum amount of waste. That is why chickpea seeds were chosen as the object of research as a source of valuable vegetable protein, which is similar in composition to animal protein and at the same time is the richest source of functional ingredients. The research used the method of analysis of literary sources that correspond to the research topic. A number of scientific works related to the sprouting and soaking of chickpea, the biological value of chickpea in the form of hummus, the prospects for processing chickpea for the production of meat and bakery products were analyzed. The paper shows the features of the general chemical composition and characteristics of individual nutrients and biologically active substances of chickpea. The given health-improving and physiological features of products from chickpea, in particular, a distinctive feature of chickpea is shown – its ability to accumulate selenium, which is absorbed 5-10 times better than from other chemical compounds. This in turn helps prevent the onset and development of cancer and other diseases. It has been shown that food preparation and heat treatment in general usually leads to a decrease in food quality and phytochemical composition of food products. However, they can inactivate thermolabile anti-nutrients, such as legume antitrypsin factors, that negatively affect protein bioavailability. Cooking food reduces unwanted factors in legumes, such as phytates, and modulates amino acid composition and protein digestibility. The regularities of increasing the biological activity of chickpea seeds during germination have been established. Based on the research results, conclusions were drawn on the formation of protein in chickpea seeds depending on the climate. On the basis of the research results, the expediency of using chickpea seeds processing products in the technology of food products with improved biological value has been theoretically substantiated and confirmed